Experimental analysis of the effect of standards on compliance and performance. Issue 2 (30th March 2017) - Boussalis, Constantine; Feldman, Yuval; Smith, Henry E.
Abstract: Legal directives – whether laws, regulations, or contractual provisions – can be written along a spectrum of specificity, about which behavioral and legal scholarship present conflicting views. We hypothesized that the combination of specificity and monitoring promotes compliance but harms performance and trust, whereas the combination of specificity and good faith enhances both the informative goal‐setting aspects of specificity and people's sense of commitment. To test these hypotheses, we used a 2x2x2 experimental design in which participants were instructed to edit a document with either general or detailed instructions, with a reference to good faith or without it, and with a review of the work or without it. Participants could engage in various levels and kinds of editing, allowing us to distinctly measure both compliance and performance. When participants require information and guidance, as in the case of editing, we found that specificity increases performance relative to the vague standard condition. We discuss the characteristics of the regulatory frameworks in which our findings are especially relevant.